Sewa Pacar Sebagai Bentuk Aktualisasi Diri Pada Tokoh Kinoshita Kazuya Dalam Video Channel YouTube Muse Indonesia Berjudul “Pacar Sewaan” Episode 2 - Ariyanto, Nazla Iftinan; Santoso, Budi (KIRYOKU, 2024)
This research aims to analyze how Kinoshita Kazuya's character tries to fulfill his self-actualization needs through rent a girlfriend. The author uses a qualitative descriptive research method. This research design uses literary psychology, specifically the hierarchy of needs from Abraham Maslow. With a humanistic approach that uses Maslow's five levels of needs, including physiological needs, safety needs, social needs, esteem needs, and self-actualization needs from Muse Indonesia's YouTube channel video entitled "Pacar sewaan" which occurs in episode 2. The results of this research show that Kazuya's character has fulfilled his self-actualization needs. This is achieved because all needs are met. 1) Physiological needs that Kazuya needs in the form of shelter and sex, 2) Kazuya's need for safety in the form of dependence and protection, 3) Kazuya's need for social needs in the form of affection, 4) Kazuya's need for esteem is maintaining a good name and self-esteem, 5) Kazuya's self-actualization needs are to show more spontaneity, simple, and natural in himself. By using the rent a girlfriend, Kazuya is motivated to prove himself to his grandmother and friends.